Prenatal Silicon Dioxide Nanoparticles Exposure Reduces Female Offspring Fertility Without Affecting Males - Min Lei; Zhenye Zhu; Chenlu Wei; Huihui Xie; Ruizhi Guo; Yanqing Zhao; Keer Wang; Mengchen Wang; Wenhui Chen; Xiqiao Xu; Xinxin Zeng; Yining Xu; et al. (Advanced Science)
Abstract Silicon dioxide nanoparticles (SiO2 NPs) are widely utilized in biomedicine due to their controllable size and biocompatibility. While previous studies have demonstrated that prenatal exposure to SiO2 NPs can traverse the placental barrier and induce neurotoxicity in offspring. However, their reproductive toxicity remains unclear. Here, it is found that prenatal SiO2 NPs exposure led to subfertility in female offspring, evidenced by decreased ovulation potential, ovarian reserve, and litter size. In contrast, male offspring maintained normal sperm production and fertility. Mechanistic analyses revealed that prenatal SiO2 NPs exposure disrupted meiotic recombination and increased oocyte apoptosis, resulting in reduced postnatal primordial follicle formation in females. Conversely, meiotic recombination occurring postnatally in male offspring remained unaffected. Notably, treatment with carboxylate (COOH)‐functionalized SiO2 nanoparticles (SiO2‐COOH NPs) has a minimal impact on fertility in female offspring. Further research, including clinical studies, is needed to confirm these findings in humans. These findings demonstrated gender‐specific reproductive toxicity induced by prenatal SiO2 NPs exposure and highlighted the importance of considering nanoparticle safety in prenatal contexts.